1‐(2H‐Tetrazolyl)‐1, 2, 4‐triazole‐5‐amine(TzTA) – A Thermally Stable Nitrogen Rich Energetic Material: Synthesis, Characterization and Thermo‐Chemical Analysis. Issue 3 (5th November 2014) - Nimesh, Sasidharan; Ang, How‐Ghee
Abstract: The targeted high nitrogen energetic material 1‐(2 H ‐tetrazol‐5‐yl)‐1, 2, 4‐triazol‐5‐amine (TzTA) was synthesized from 3‐amino‐1, 2, 4‐triazole via a two‐step procedure using cyanogen bromide and sodium azide. TzTA was prepared in good yields and characterized using analytical (elemental) and spectroscopic (IR, Raman, NMR) techniques. The crystal structure of sulfate salt of the molecule was solved by means of low temperature X‐ray crystallography, which showed the co‐planarity of the two rings. The sulfate salt of the molecule crystallized in monoclinic system P 21/ n, with a crystal density of 1.856 g cm −3 . The thermal stability of the molecule was assessed by DSC. The molecule showed excellent thermal stability better than many known nitrogen rich energetic molecules and showed comparable thermal stability with HMX. Non‐isothermal kinetics was performed on the molecule to derive the activation energy. Constant volume combustion energy was determined using oxygen bomb calorimeter and back calculated the heat of formation. Preliminary insight on the gas generating capability of the molecule was tested by measuring the dynamic pressure generated inside a closed bomb. Dynamic pressure of an oxygen balanced system (TzTA and ADN) was also measured using the Parr dynamic pressure measurement system. Abstract :